2020
DOI: 10.1016/j.jiph.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and comorbidities: Deleterious impact on infected patients

Abstract: The pandemic situation with the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from China has endangered human lives. Coronavirus disease 2019 (COVID-19) is presented with asymptomatic, mild, or severe pneumonia-like symptoms. COVID-19 patients with diabetes, chronic obstructive pulmonary disease (COPD), cardiovascular diseases (CVD), hypertension, malignancies, HIV, and other comorbidities could develop a life-threatening situation. SARS-CoV-2 utilizes ACE-2 receptors found at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
682
8
93

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 819 publications
(838 citation statements)
references
References 54 publications
55
682
8
93
Order By: Relevance
“…Certain co-morbidities were associated with strong angiotensin-converting enzyme 2 (ACE2) receptor expression. ACE2, a cleavable, extracellular enzyme located on the cell surface membrane, mediates entry by SARS-CoV-2 into human cells, leading to significant morbidity and mortality [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain co-morbidities were associated with strong angiotensin-converting enzyme 2 (ACE2) receptor expression. ACE2, a cleavable, extracellular enzyme located on the cell surface membrane, mediates entry by SARS-CoV-2 into human cells, leading to significant morbidity and mortality [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, diabetes mellitus was identified as the most significant co-morbidity (with a high OR = 9.4) associated with COVID-19 mortality. People with diabetes are susceptible to SARS-CoV-2 infection due to impaired phagocytic cell capabilities, in addition to several risk factors, including elevated ACE2 receptors levels, impaired T-cell function, and increased interleukin-6 concentration, which enhances viral entry into the cells, resulting in an escalation in lung inflammation and poor outcomes [ 26 ]. Although diabetes was independently associated with COVID-19 mortality in the current study, other co-morbidities, including hypertension, CVD, CKD, and obesity, were also linked to COVID-19 deaths, and the synergistic effect of these factors may have contributed to promoting COVID-19 mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response of patients having comorbidities might be weaker and less effective in containing the virus. Respiratory diseases and cardiovascular diseases, hypertension, diabetes, and diseases affecting the immune system are associated with significant morbidity and mortality [ 24 ]. As COVID-19 progresses, it can lead to hyper-inflammatory responses and cytokine storms [ 25 ].…”
Section: Pathogenesis Of Covid-19 In Light Of the Damage–responsementioning
confidence: 99%
“…Furthermore, the current data reveal the SARS-CoV-2 mortality rate between 3% and 5, which is much lower than other Coronaviridae family member’s mortality rate, such as SARS-CoV (9–15%) and MERS-CoV (34–37%) [ [7] , [8] ]. However, tragically, SARS-CoV-2 is considerably transmissible and causes more severe health effect on the elderly people or with comorbidities, which is the existence of more than one chronic disease such as diabetes, obesity, and cardiovascular at the same time, that weaken the immune system of the human body [ [9] , [10] ]. The risk for severe illness from SARS-CoV-2 increases with age; older adults above 65 years of age are at higher risk (23-fold) and account for 80% of hospitalizations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%